Nuevas evidencias históricas del siglo XVIII sobre la presencia de “cardos” en Argentina y sus implicancias etnobotánicas - Gutiérrez, Diego Germán (2020)
Background and aims: Currently, many species called “thistles” are widely distributed in Argentina. During 18th Century several Jesuit publications mentioned “thistles” as the work made by Florian Paucke. The goal of this work is to gather, from writing sources of the 18th Century, plant records called as “thistles” or similar names; to identify at species level the plant entities mentioned by Paucke as “azafrán”, “cardo”, and “cardo hortense”; and to discuss ethnobotanical implications. M&M: The study area included Argentina from the Pampean region to the Chacoan region. Historical evidences of the 18th Century, herbarium materials and their morphology were analyzed, and field trips were made. Results: Entities “azafrán alazor”, “de Indias” o “paracuario” by Paucke were identified as Carthamus tinctorius (“safflower”), and “cardo” and “cardo hortense” as Cynara cardunculus (Compositae), associated with varieties sylvestris (“thistle”) and scolymus (“artichoke”), respectively. “Cardo santo” named by Pedro de Montenegro was associated to Argemone subfusiformis (Papaveraceae). Twelves new medicinal and food uses of the Moqoit from the Chaco of Argentina were recorded.